2021
DOI: 10.1057/s41301-021-00305-0
|View full text |Cite
|
Sign up to set email alerts
|

A Trade Agenda for the Right to Food

Abstract: Whoever benefits from a trade regime in effect gains power over significant aspects of different food systems. And yet the WTO still does not provide a coherent food policy and the 2021 UN Food Systems Summit made very little space for trade policy. The degree of international trade policy discord and supply chain fragility strongly suggests that there must be new international trade negotiations around fundamental questions of principle. Seeing little benefit in reforming the WTO, this article explains how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…At the root of the barriers explored during the Forum are unjust power dynamics, which tend to work against workers' interests. There is growing recognition of the need to address power imbalances within food systems, as highlighted by the UN Special Rapporteur on the Right to Food Michael Fakhri and others concerned with corporate domination of the recent UN Food System Summit (Clapp, 2021;Clapp et al, 2021;Fakhri, 2021). As Clapp notes, a small number of large companies bear huge influence on how food is produced and conditions for food system workers, with profit prioritized over livelihoods (2021).…”
Section: Summary Of Current Challengesmentioning
confidence: 99%
“…At the root of the barriers explored during the Forum are unjust power dynamics, which tend to work against workers' interests. There is growing recognition of the need to address power imbalances within food systems, as highlighted by the UN Special Rapporteur on the Right to Food Michael Fakhri and others concerned with corporate domination of the recent UN Food System Summit (Clapp, 2021;Clapp et al, 2021;Fakhri, 2021). As Clapp notes, a small number of large companies bear huge influence on how food is produced and conditions for food system workers, with profit prioritized over livelihoods (2021).…”
Section: Summary Of Current Challengesmentioning
confidence: 99%
“…I have suggested that the 2021 Summit can also be understood as an inter-corporate contest between the newer “green” agri-food businesses (practicing so-called sustainable intensive agriculture) versus the older industrial intensive agrifood sector – with both parties substantively ignoring social justice and human rights (Fakhri, 2021b ). The world’s food systems have been dominated by corporations and marked by crisis for at least the last 60 years.…”
Section: Sustainable Intensive Agriculture Vs Industrial Agriculturementioning
confidence: 99%
“…131–132). As Fakhri States, the AA has not achieved a liberal global market and has not benefited developing countries, but has been favoring powerful States and their corporations (UNGA, 22 July 2020, p. 7; Fakhri, 2021, p. 215).…”
Section: Introductionmentioning
confidence: 99%